PENGARUH FASILITAS KERJA DAN KARAKTERISTIK PEKERJAAN TERHADAP KEPUASAN KERJA DALAM UPAYA MENINGKATKAN KINERJA PEGAWAI DI KANTOR PELAYANAN PAJAK PRATAMA TEBING TINGGI - Sari Ulina Parangin-Angin (Universitas Islam Islam Sumatera Utara, 2020)
The formulation of the problem in this research is how the influence of work facility on job satisfaction. How influence of job characteristic on job satisfaction. How influence of work facility on employees performance. How influence of job characteristic on employees performance. How influence of work satisfaction on employees performance.The purpose of this research is for know influence of work facility on job satisfaction. How influence of job characteristic on job satisfaction. For know influence of work facility on employees performance. For know influence job characteristic on employees performance. For know influence work satisfaction on employees performance. The sample in this research is 95 employees, with data analysis technique used is path analize. The results of this research explain that work facility effect has a positive and significant on employee job satisfaction. Job Characteristic effect has a positive and significant on employee job satisfaction. Work facility effect has a positive and significant on employee performance. Job characteristic effect has a positive and significant on employee performance. Job satisfaction effect has a positive and significant on employee performance.